An Intertextual Analysis of “Menombak Matahari”, “Sarpakuda”, and Babad Mangir Suradipura - Faqih Sulthan; Testiana Deni Wiajayatiningsih (University of Surakarta, 2024)
The creation of a new text is highly influenced by previous texts, known as intertextual relationships. For instance, the short stories